Does the mismatch negativity operate on a consciously accessible memory trace? - Dykstra, Andrew R.; Gutschalk, Alexander (Science advances, 2015)
The extent to which the contents of short-term memory are consciously accessible is a fundamental question of cognitive science. In audition, short-term memory is often studied via the mismatch negativity (MMN), a change-related component of the auditory evoked response that is elicited by violations of otherwise regular stimulus sequences. The prevailing functional view of the MMN is that it operates on preattentive and even preconscious stimulus representations. We directly examined the preconscious notion of the MMN using informational masking and magnetoencephalography. Spectrally isolated and otherwise suprathreshold auditory oddball sequences were occasionally random rendered inaudible by embedding them in random multitone masker “clouds.” Despite identical stimulation/task contexts and a clear representation of all stimuli in auditory cortex, MMN was only observed when the preceding regularity (that is, the standard stream) was consciously perceived. The results call into question the preconscious interpretation of MMN and raise the possibility that it might index partial awareness in the absence of overt behavior. - A change-related component of the auditory evoked response long thought to be preattentive and preconscious may actually require consciousness. - A change-related component of the auditory evoked response long thought to be preattentive and preconscious may actually require consciousness.
Gesehen am 02.07.2020